PERGESERAN CARA PANDANG MASYARAKAT MUSLIM SUKU ALOR TERHADAP LARANGAN PERKAWINAN SATU SUKU (ENDOGAMI) DI KOTA ATAMBUA-NUSA TENGGARA TIMUR - Roykhatun Nikmah (JOURNAL EQUITABLE, 2018)
Many previous studies have discussed the themes of endogamy and exogamy marriage, but the differences in the characteristics of this study are that the people studied are in the majority Catholic region, and consist of various ethnicities and cultures. For the Alor Muslim community who still prohibit endogamous marriage due to biological and geneological reasons. Changes in the times and development of society changed the thinking paradigm of some Alor people regarding the prohibition of endogamous marriages that were becoming obsolete. This study wants to see what factors influence the shift in perspective and how the relationship between the Customary, Islamic and State legal systems influences each other in the Alor tribal system in general. John R Bowen's legal pluralism theory is used to explain the three legal systems that apply in the life of the Muslim community of the Alor people in Atambua. While the theory of customary law and Islamic struggle is used to see the extent of the dialogue between the two legal systems in understanding the prohibition of endogamous marriage